HAuCl4, Putative General Aquaporins Blocker, Reduces Platelet Spreading, Filopodia Formation, Procoagulant Response, and Thrombus Formation Under Flow - Misztal, Tomasz; Golaszewska, Agata; Branska-Januszewska, Justyna; Marcinczyk, Natalia; Chabielska, Ewa; Tomasiak, Marian; Rusak, Tomasz (Frontiers in Physiology, 2020)
Background: Recent studies indicate that aquaporin water channels (AQPs) have a regulatory function in human platelet secretion and in procoagulant response of murine platelets. However, the engagement of AQPs in morphological changes, procoagulant response and thrombus formation in human blood has never been investigated. Methods: Confocal microscopy was used to study platelet spreading, filopodia formation, ballooning, and thrombus formation under flow. Flow cytometry was utilized to assess platelet phosphatidylserine (PS) exposure and microparticles shedding. Kinetics of clot formation in vitro was evaluated by thromboelastometry. Mouse model of FeCl3-induced thrombosis was used to investigate thrombus formation in vivo. Results: We found that HAuCl4, a classical AQP inhibitor (10-100 µM), reduced spreading of human platelets on collagen-coated surfaces and inhibited filopodia formation in a fluid phase. Under flow conditions, HAuCl4 (100 µM) attenuated thrombi growth on collagen, platelet secretion and PS exposure. Thrombus formation was restored by the addition of exogenous ADP. Collagen-evoked platelet procoagulant response (evaluated as PS exposure, shedding of microparticles, platelet-dependent thrombin generation, and membrane ballooning) was distinctly reduced by HAuCl4 (25-200 µM), as well as the dynamics of clot formation. In mouse model of thrombosis, reduction of PS-positive platelets within thrombus was observed in the presence of HAuCl4 (1-10 mg/kg). Conclusions: These results suggest that in human platelets AQPs are crucial for agonist-evoked morphological changes, thrombus formation under flow and in development of procoagulant response. Antithrombotic effect in vivo suggests that nontoxic inhibitors of AQPs may be considered as potential candidates for a novel class of antiplatelet drugs.